Good Governance and Strengthening the Management of Civil Servant Towards to World Class Bureaucracy - Herawaty, Herawaty (Faculty of Law Cenderawasih University, 2017)
Bureaucracy as a system of organizing state apparatus with a very broad and complex task is very necessary in controlling the operation of government management, but the performance of bureaucracy and routine activities of officials and bureaucratic apparatus often cause new problems. This new problem makes the bureaucracy static, less sensitive to the social environment, even seem likely to be resistant to the renewal. This situation often raises the potential of potential mal-administration practices on corruption, collusion and nepotism (KKN) praxes and the decline in public services. Starting from such bureaucratic conditions, bureaucracy reform and good governance are the main pillars and the central point in creating State Civil Apparatus Management becomes a necessity towards world-class bureaucracy.